Diálogo inter-religioso : tensões e perspectivas na interpretação da instrução diálogo e anúncio à luz da proposta teológica de Jacques Dupuis - Silva, José Barbosa da (2013)
This research aims to analyze the challenges and prospects of interreligious dialogue from the innovations proposed by Vatican II, as well as its implications in several documents in the post-conciliar period, particularly in the Intruction Dialogue and Proclamation. Faced with the failure of the Magisterium of the Church in addressing the issue, the controversies raised in the various spheres of ecclesial institution, Theology of Religious Pluralism by Jacques Dupuis can better locate the problem by proposing that all religions are included in God's plan of salvation for all mankind, recognizing them as ordinary paths of salvation. The attitude of the Church in relation to non-Christian religions has been marked by ambiguity, breaking thus with the pastoral guidelines issued by the Council that urges Christians to discover the positive values of these religious traditions. In this sense, the Declaration Dominus Iesus, will open a crusade against the theologians supporters of pluralism in order to stop the advance of this new paradigm for theology, fomenting a speech with exclusivist tendencies that fails to engage in a dialogue with the modern world, plural and secular.